Gambaran Attachment Anak dengan Orangtua di Era Perkembangan Teknologi dilihat dari Persepsi Anak (Studi pada siswa-siswi SD X) - Elizabeth Nasya; Riana Sahrani; Debora Basaria (Provitae: Jurnal Psikologi Pendidikan, 2021)
Attachment security is defined as a condition where an individual has a sense of security and is not disturbed by the availability of someone who is considered as an attachment figure (Ainsworth, Blehar, Waters, & Wall in Solomon & George, 2008). Ainsworth classifies the types of attachments into secure attachment and insecure attachment, where insecure attachment is further divided into ambivalent attachment and avoidant attachment (Solomon & George, 2008). This study analyzes data using two main dimensions, namely secure and insecure. The purpose of this study is to provide an overview of children’s attachment in today’s digital era seen from the perception of the children. The research data was collected in March 2020 using purposive sampling, which involved 72 participants who filled out the research questionnaire directly with paper-and-pencil tests. Criteria for participants in this study are children in the age range of 9-11 years who, at the time of the study, were elementary school level students. Based on the results of data collection, a percentage of 100% of the total of subjects were gadget users. Based on research data using descriptive techniques, it was found that there were more subjects in the study who showed a tendency to have secure attachment compared to insecure attachment.